Ethics and Professional Deontology as a Course in the Accounting and Finance degree: An Empirical Study - Carreira, Francisco (2011)
Nowadays, the great challenge that faces the economy is to be able to reconcile economic sustainable growth with ethical and moral values. Ethics plays an important role in organizations and society that have a great concern with environment, social and economic issues that require a greater social consciousness and rational human behaviour. In this work, the authors analyse the role of ethics and moral values in the higher education, as well as the articulation with two impoltant professions on the financial area. The first one is Chartered Accounts as in Portuguese Official Technician of Accounts (TOC) and the second one is Auditor Accounts as in Portuguese Statutory Auditor (ROC). Then, the authors compared the ethical guidelines used by both professions. To achieve their purpose, the authors handed out a questionnaire with several questions about ethical behaviour and rules of Ethics to a sample of higher education students of the third year of an Accounting and Finance Curse in the Business Administration College of the SeHtbai Polytechnic Institute. This questionnaire was applied before the beginning of the semester of the Ethics subj ect. Afterwards, the authors applied the same questionnaire to those students who would like to become Chartered Accounts and Statutory Auditors. Finall y, with this data, the authors carried out a statistic analysis that summarises the questionnaire categorising in several clusters, as result of cluster analysis, according to the variables that had higher scores. The results of this research confinn the initial hypothesis that Higher Education Students of the third year of an Accounting and Finance Curse in the Business Administration College of the Selltbal Polytechnic Institute do not know the limitations of the Ethical Behaviour.